Inter-Religious Marriage: A Controversial Issue in Indonesia (Faculty of Law, Universitas Negeri Semarang, 2022)
Different religious marriages we often encounter during society especially among the affluent and celebrities. This kind of marriage has been done by Muslim men married to non-Muslim women or otherwise Muslim women married to non-Muslim men. Sometimes in response we only follow the understanding of some people who greatly glorify freedom in all fields (Liberal), although it is in terms of a very private as well as religion. In a liberal sense the beliefs of religious differences in marriage are not a problem. Liberalism is a notion that requires the freedom of individuals in all fields. This study is intended to analyze the legal basis of inter-religious marriage or mixed marriage in Indonesia. This study highlighted and found that inter-religious marriage is become complicate problem when trying to determine some basic rights, including the property, child, and the others.